DEEP STRUCTURE OF THE MID BLACK SEA HIGH (OFFSHORE TURKEY) IMAGED BY MULTI-CHANNEL SEISMIC SURVEY (BLACKSIS CRUISE) - Rangin C.; Bader A.G.; Pascal G.; Ecevitoǧlu B.; Görür N. (My University, 2002)
The Black Sea is considered to be a Mesozoic–Early Cenozoic marginal basin related to the north-dipping subduction of Tethys beneath Europe. However deformation of this basin during the successive Eocene to Neogene collisions of African-derived continental fragments (Kirshehir and Arabian micro plates) remains poorly understood. A multi-channel seismic survey conducted in the central part of the Black Sea has shed light on the superimposed tectonic fabrics of the Central Ridge (the Mid Black Sea High, MBSH) in response to these successive collisions. The MBSH is formed by a series of large NW–SE trending anticlines and synclines, and possible northeast-verging thrusts were identified at the boundary with the deep East Black Sea Basin northeast of the ridge. These buried folds and thrusts, blanketed by 3 to 8 s TWT of undeformed sediments, are interpreted as the offshore extension of the Early Cenozoic tectonic belt resulting from the collision between the Pontides in the north and the Kirshehir block to the south. The offshore part of the belt forming the ridge could have then collapsed when collision ended. Neogene structures also affect the MBSH. A recent graben (the Sinop Trough) extends between this central high and mainland Turkey. This graben could have been formed during the late Miocene incipient dextral strike slip motion of the North Anatolian Fault that was initiated during extrusion of the Anatolian microplate. Active tectonic inversion of deep-seated normal faults present along the Pontides passive margin was also observed along the northeastern flank of the Eastern Pontides. This deformation is the westernmost extension of the Lesser Caucasus front that outlines the suturing of the Eastern Black Sea Basin in easternmost Turkey and in Georgia.